The Normative Implications of "Knowing the Future" for Preventive War. Issue 3 (2nd July 2016) - Colonomos, Ariel
ABSTRACT: What if claims about the future informed us about the intentions and the capabilities of our opponents to wage war against ourselves? Would and should the existing norms that restrict the preventive use of force change in the wake of such transformation? This article highlights the potential normative consequences of this change and discriminates between several possible normative evolutions. Would and should the "knowability of the future" alter radically the traditional rule of self-defense? This rule could indeed be jeopardized but, as I argue in this paper, it should not (and might not necessarily). However, the distinction between preemption and prevention could become obsolete. Future claims about security will also induce new security doctrines as knowledge about the future would be used to signal one's intentions and deter one's opponent. This change would also have a significant impact on accountability, as citizens would have a more active role in discussions over foreign policy. Moreover, new modes of predictions and forecasting will challenge the traditional role of experts whose biases have hampered their analyses and anticipations. Thus, trustworthy future claims could bring significant progress in both ethical and political terms as they would trigger a debate on the role of knowledge in democratic societies.